Kelayakan Usahatani Cabai Merah Monokultur Lahan Sawah dengan Sistem Irigasi Manual di Kapanewon Galur Kabupaten Kulon Progo - Yudha, Bintang Kusuma; Fivintari, Francy Risvansuna (Universitas Galuh, 2025)
Red chili is one of the horticultural commodities that has the potential to be developed because it has high economic value. This study aims to analyze the cost, revenue, income, profit, and feasibility of monoculture red chili farming in paddy fields with manual irrigation systems in Kapanewon Galur. Determination of respondents using the census method so that the samples taken were 28 farmers. The results showed that the production costs incurred by monoculture red chili farmers in paddy fields with manual irrigation systems per 1.239,6 m2 amounted to Rp 13.746.754,9, by obtaining receipts of Rp 21.331.647,11, revenues of Rp 11.710.329,95, and profits of Rp 7.584.892,26. The feasibility of monoculture red chili farms in paddy fields with manual irrigation systems in Kapanewon Galur is seen from the R/C of 1,55, land productivity of Rp 6.474,17/m2 , labor productivity of Rp 311.481,75/HKO, and capital productivity of 80,62%.